2014
DOI: 10.1038/nmeth0914-972
|View full text |Cite
|
Sign up to set email alerts
|

Addendum: Independent optical excitation of distinct neural populations

Abstract: all variants to have similar photocurrents in cultured neurons (Fig. 1d,e). However, we observed more cytosolic aggregates with the KGC version and a reduction of aggregates with the ER2 version (Supplementary Fig. 2). It is therefore likely that CsChrimson will be of use with the ER2 trafficking sequence in some biological contexts. methods Methods and any associated references are available in the online version of the paper. Accession codes. GenBank/EMBL/DDBJ: CsChrimson is listed under accession code KJ995… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…In this study, we compared the ion selectivity of our previously published XXL and XXM and found that XXM showed a four-fold increased Na + selectivity over H + together with a two-fold increased K + selectivity over H + , compared to wild type ChR2. Based on this finding, we made further aspartate to histidine and cysteine mutations of PsChR (Platymonas subcordiformis channelrhodopsin) [20] and Chronos [9]. PsChR wild type was already reported to be highly Na + conductive and indeed showed a six-fold increased Na + and K + selectivity over H + compared to wild type ChR2 in our measurements.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…In this study, we compared the ion selectivity of our previously published XXL and XXM and found that XXM showed a four-fold increased Na + selectivity over H + together with a two-fold increased K + selectivity over H + , compared to wild type ChR2. Based on this finding, we made further aspartate to histidine and cysteine mutations of PsChR (Platymonas subcordiformis channelrhodopsin) [20] and Chronos [9]. PsChR wild type was already reported to be highly Na + conductive and indeed showed a six-fold increased Na + and K + selectivity over H + compared to wild type ChR2 in our measurements.…”
Section: Introductionmentioning
confidence: 81%
“…Such changes can also be engineered by point mutations. In this study we compared the properties of ChR2, Chronos [9], PsChR [20], and their corresponding mutants of the aspartate in TM4 (DC gate aspartate).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The following fly lines were used: MBON split-Gal4 lines (28);n 20xUAS-CsChrimson-mVenus (attP18) (36); 10xUAS-Chrimson88-tdTomato3.1 (attp18) (David Anderson lab); UAS-Shibire ts (37); 20xUAS-Shibire ts (38); 20xUAS-gtACR1 (39); UAS-Kir2. 1 (40); DAN split-Gal4 lines (28); w 1118 ; pBPp65ADZpUw (attP40); pBPZpGAL4DBDUw (attP2) (Empty Split) (41); 20xUAS-dsFRT-CsChrimson-mVenus (42) ; LexAop-FLP (43) ; scr-LexA (44).…”
Section: Methodsmentioning
confidence: 99%